The Concept of Fitrah as a Paradigm of Islamic Education: Perspective of The Quran - Ghalib, H. M.; Mujahid, Achmad; Suarni, Suarni (Prodi Pendidikan Agama Islam FTIK IAIN Palopo, 2022)
This study aims to describe the concept of fitrah as a paradigm of Islamic education according to the Koran. This qualitative research uses the descriptive-analytical method. All data from written materials related to the variables will be discussed and relevant. The concept of fitrah is a character, temperament, origin, religion, and all inherent potential, which is a gift from Allah Swt. Every human child born from his mother’s womb will always be accompanied by nature as the basis for personality formation in living his life. Human psychological components related to nature include human structure (physical, spiritual, nafsani, heart, reason, and lust), al-hayah (vitality), al-khuluq (character), al-sajiah (skills or talents), heredity (heredity), intuition (the ability to receive inspiration from god) and al-amal (behavior).